Revisiting Folger's pouch in double-chambered right ventricle - Sakshi Sachdeva; Dheeraj Deo Bhatt; Dinesh Kumar (Wolters Kluwer Medknow Publications, 2022)
Folger's pouch is a right ventricular outflow pouch arising from the distal low-pressure chamber in double-chambered right ventricle. It is rarely described on echocardiogram due to difficult visualization and lack of knowledge of its existence. Retrospective assessment of echocardiogram after an angiocardiographic evaluation demonstrates the pouch in a modified high parasternal view.